Community Perceptions and Participation in Mangrove and Coral Reef Conservation: Implications for Sustainable Coastal Ecosystem Management in Sendang Biru, Indonesia - Rif’an Habibi; Charlotte Thorns (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to analyze community perceptions and participation in mangrove and coral reef conservation and to evaluate their implications for sustainable coastal ecosystem management in Sendang Biru, Malang Regency, Indonesia. Methodology: A quantitative descriptive research design was employed using a structured questionnaire survey involving 97 respondents selected from a population of 2,841 coastal residents through proportionate random sampling. Data were analyzed using descriptive statistical techniques based on perception scores and percentage distributions. Main Findings: The results indicated that community perceptions of mangrove and coral reef conservation were generally positive, particularly regarding environmental benefits. Approximately 76% of respondents were familiar with mangrove ecosystems, and 68% recognized their environmental benefits. Environmental perception scores for mangrove and coral reef conservation were 164 and 183, respectively, while economy perception scores reached 115 and 105. In contrast, perceptions of economic benefits differed between ecosystem types, with mangrove conservation receiving a negative score (T = 68) and coral reef conservation a positive score (T = 159). Community support for conservation initiatives was high (T = 180), but willingness to participate directly in conservation activities remained low (T = 82). Novelty/Originality of this study: This study provides an integrated assessment of community perceptions and participation in both mangrove and coral reef conservation within a coastal ecosystem management framework. The findings reveal an awareness–participation gap, demonstrating that positive conservation perceptions and support do not necessarily translate into active participation, highlighting the need for more participatory and community-based conservation strategies.